2020
DOI: 10.1088/1361-6404/abb56a
|View full text |Cite
|
Sign up to set email alerts
|

LGBT+ physicists qualitative experiences of exclusionary behavior and harassment

Abstract: This article looks at the qualitative survey responses of LGBT physicists about their experiences of exclusionary behavior and harassment. Of the 324 respondents 71 reported such an experience and gave a qualitative response. Findings indicate that the majority of respondents experienced exclusionary behavior based on their gender expression or being a woman. The behavior came mostly in the forms of verbal comments and social exclusion, with fewer participants reporting physical touching or sexual harassment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…An emerging body of literature focused on the experiences of LGBQ (lesbian, gay, bisexual, and queer) individuals, as well as people who identify as trans, gender non-conforming, and nonbinary (often abbreviated as TGNC), also face inequitable conditions hindering their full participation in STEM. This research shows that LGBQ people face discrimination in STEM workplaces (Barthelemy, 2020;Cech & Rothwell, 2019;Yoder & Mattheis, 2016), and within their undergraduate programs (Cech & Waidzunas, 2011;Cooper & Brownell, 2016). These conditions have led to a marked disparity between heterosexual students and their sexual minority peers in terms of persisting within STEM undergraduate degree programs (Hughes, 2018), despite prior academic preparation, interest in STEM as a career, and participation in programs like undergraduate research shown to promote retention in STEM.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…An emerging body of literature focused on the experiences of LGBQ (lesbian, gay, bisexual, and queer) individuals, as well as people who identify as trans, gender non-conforming, and nonbinary (often abbreviated as TGNC), also face inequitable conditions hindering their full participation in STEM. This research shows that LGBQ people face discrimination in STEM workplaces (Barthelemy, 2020;Cech & Rothwell, 2019;Yoder & Mattheis, 2016), and within their undergraduate programs (Cech & Waidzunas, 2011;Cooper & Brownell, 2016). These conditions have led to a marked disparity between heterosexual students and their sexual minority peers in terms of persisting within STEM undergraduate degree programs (Hughes, 2018), despite prior academic preparation, interest in STEM as a career, and participation in programs like undergraduate research shown to promote retention in STEM.…”
Section: Introductionmentioning
confidence: 91%
“…Congruent with these findings, a report commissioned by the American Physical Society determined that LGBT+ physicists felt compelled to hide or cover their sexual orientations and gender identities, resulting in feeling isolated and considering leaving their workplaces (Atherton et al, 2016). In a follow-up study, Barthelemy (2020) found gender harassment in physics especially common for LGBT+ physicists, particularly among women. Linley, Renn, and Woodford (2018) also found students reported STEM classrooms to be less safe than those in the social sciences and humanities.…”
Section: Lgbq Climate In Stemmentioning
confidence: 98%
“…According to Hitlan and Noel (2009), withdrawal behaviour includes harassing, avoiding, excluding, or intimidating behaviours directed at others and is linked to a variety of negative emotional states, such as sadness, loneliness, jealousy, guilt, embarrassment, and social anxiety (Barthelemy, 2020). The definition of withdrawal behaviour in the workplace is the exclusion, rejection, or disregard of an individual (or group) by another individual (or group), which hinders the development or maintenance of positive interpersonal connections, professional success, or a positive reputation in the workplace.…”
Section: C) Exclusionary (Withdrawal) Behaviourmentioning
confidence: 99%
“…An emerging body of work in PER centers queer and trans* (QT) physicists' experiences [1,2]. Cisheteronormative climates across physics departments shape oppressive experiences for undergraduate QT students, including encounters of homophobic remarks, lack of queer-affirming faculty support, and sexual harassment [1,3]. Some physicists conceal their queer identities to avoid being subjected to exclusionary behaviors.…”
Section: A Queer Experiences and Intersectionality In Permentioning
confidence: 99%